2016
DOI: 10.1186/s11671-016-1704-2
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Programmed Cell Death in Neurotoxicity of Metallic Nanoparticles: Recent Advances and Future Perspectives

Abstract: The widespread application of metallic nanoparticles (NPs) or NP-based products has increased the risk of exposure to NPs in humans. The brain is an important organ that is more susceptible to exogenous stimuli. Moreover, any impairment to the brain is irreversible. Recently, several in vivo studies have found that metallic NPs can be absorbed into the animal body and then translocated into the brain, mainly through the blood–brain barrier and olfactory pathway after systemic administration. Furthermore, metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 132 publications
(110 reference statements)
0
21
0
Order By: Relevance
“…Studies using animal models have demonstrated that different types of NPs (i.e., Au, TiO 2 , SiO 2 , carbon, and QDs) are able to cross the placenta and transfer to vulnerable fetus causing variable toxic effects on fetal brain, nerve development and future fertility [14]. In particular, to metallic NPs, some studies have documented that exposure during pregnancy can affect fetal brain development [75][76][77], and underlined that much attention should be paid to the role of apoptosis in developmental neurotoxicity induced by NPs [12]. In addition to TiO 2 NPs and silver NPs that were most widely studied, other metallic nanomaterials including NPs of iron oxide among others should be investigated to understand the pivotal role of apoptosis in the neurotoxicity of NPs and to determine the consequences of IONP exposure on embryo and fetal development [12,54].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using animal models have demonstrated that different types of NPs (i.e., Au, TiO 2 , SiO 2 , carbon, and QDs) are able to cross the placenta and transfer to vulnerable fetus causing variable toxic effects on fetal brain, nerve development and future fertility [14]. In particular, to metallic NPs, some studies have documented that exposure during pregnancy can affect fetal brain development [75][76][77], and underlined that much attention should be paid to the role of apoptosis in developmental neurotoxicity induced by NPs [12]. In addition to TiO 2 NPs and silver NPs that were most widely studied, other metallic nanomaterials including NPs of iron oxide among others should be investigated to understand the pivotal role of apoptosis in the neurotoxicity of NPs and to determine the consequences of IONP exposure on embryo and fetal development [12,54].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the particles accumulate in autophagosomes. Researchers have raised concerns about the impact the fetal and neonatal brain may suffer from altered autophagy activity from exposure to silver (Guo et al, 2017 ) and titanium dioxide nanoparticles (Song et al, 2016 ), as well as even smaller Cadmium Selenide / Zinc Sulfide (CdSe/ZnS) quantum dots (Chen et al, 2013 ).…”
Section: Discussion Of Environmental Exposuresmentioning
confidence: 99%
“… 65 From there, they can slowly diffuse toward all organs including the brain through the systemic blood circulation or the lymphatic vessels. 110 , 112 NPs can induce various biological responses: inflammatory response, oxidative stress, modulation of gene expression, effects on cell cycle control, and proliferation. 109 NPs can be recognized by the immune system, following any route of uptake into the organism.…”
Section: Link Between Oms and Nps And Potential Actions Of Hrsmentioning
confidence: 99%
“…Repeated exposure to NPs causes oxidative stress, cytotoxicity, and autophagy, 119 suppresses inflammation, and secretes proinflammatory cytokines. 112 , 120 Cytokines, as IL-1, can be directly produced by microglia and act on the pituitary axis, 121 which can, in turn, activate the immune system with its hormones secretion such as cortisol. 121 Leucocytes also possess adrenalin, steroids, insulin, prolactin, growth hormone, and thyroxine receptors.…”
Section: Link Between Oms and Nps And Potential Actions Of Hrsmentioning
confidence: 99%